2012
DOI: 10.1158/1940-6207.capr-11-0370
|View full text |Cite
|
Sign up to set email alerts
|

Blood Cell Origin of Circulating MicroRNAs: A Cautionary Note for Cancer Biomarker Studies

Abstract: Circulating, cell-free microRNAs (miRNAs) hold great promise as a new class of cancer biomarkers due to their surprisingly high stability in plasma, association with disease states, and ease of sensitive measurement. Yet little is known about the origin of circulating miRNAs in either healthy or sick people, or what factors influence levels of circulating miRNA biomarkers. Of 79 solid tumor circulating miRNA biomarkers reported in the literature, we found that fifty-eight percent (47/79) are highly expressed i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
784
4
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 799 publications
(823 citation statements)
references
References 29 publications
27
784
4
8
Order By: Relevance
“…Small nuclear U6 is less stable in fluids than in tissues, [7] whilst miR-16 is a red blood cell expressed miRNA, and variations in blood cell count and/or any hemolysis could have important implications. [19] Interestingly, highly expressed circulating miR-16 [14] and peripheral blood mononuclear cell miR-16 [15] levels have themselves been shown to discriminate PDAC from HC, and those with benign disease. Therefore, the combined use of snU6 and miR-16 might not be appropriate as endogenous control, whereas a miRNA with the least change in expression across the various samples in the array could have been chosen as a normalizer.…”
Section: Expert Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…Small nuclear U6 is less stable in fluids than in tissues, [7] whilst miR-16 is a red blood cell expressed miRNA, and variations in blood cell count and/or any hemolysis could have important implications. [19] Interestingly, highly expressed circulating miR-16 [14] and peripheral blood mononuclear cell miR-16 [15] levels have themselves been shown to discriminate PDAC from HC, and those with benign disease. Therefore, the combined use of snU6 and miR-16 might not be appropriate as endogenous control, whereas a miRNA with the least change in expression across the various samples in the array could have been chosen as a normalizer.…”
Section: Expert Commentarymentioning
confidence: 99%
“…Importantly, the majority of circulating miRNAs might originate from blood rather than cancer cells. [19] Furthermore, co-expression of miRNAs in different diseases might reflect a general inflammatory response. Hence, bloodbased miRNA expression could be a non-specific indicator of a tumor, rather than tissue-origin-specific.…”
Section: Expert Commentarymentioning
confidence: 99%
“…And, most of the studies so far have evaluated the expression of miRNAs using formalin-fixed paraffin-embedded (FFPE) samples. Pritchard and colleagues found that 58% of the solid tumor-associated circulating miRNA biomarkers were highly expressed in blood cells, and levels of these biomarkers were correlated with blood counts (68). Therefore, they hypothesized that the levels of circulating miRNAs might reflect blood counts, rather than correlate with a cancer-specific origin.…”
Section: Challenges In the Use Of Mir-451 As A Biomarkermentioning
confidence: 99%
“…Erythrocyte haemolysis has been reported to alter miRNA measurements in whole blood, plasma, serum and tissues ( McDonald et al , 2011; Pritchard et al , 2012). The total RNA extracted using the three different methods was examined for degree of haemolysis by quantifying miR-451-5p and miR-23a-3p ( Dataset b).…”
Section: Resultsmentioning
confidence: 99%